Transformations in the atmospheric circulation in the West Antarctic sector and Applications for the weather forecasts - V. E. Timofeuev (Ukrainian Antarctic Journal, 2016)
Temporal Stability and transformation in the atmospheric circulation in summer and winter seasons is studied by means of assistance Markov’s process. It is shown that initial state atmosphere can be presented by the most probable pressure field. The simplest transformation is realized in the months with positive air temperature anomaly and comprises in series of cyclones, along with migrative wedges. Temporal stability of an individual synoptic process, associated with the etalon pressure fields is found to be longer in the winter season, and the most probable pressure fields are more stable than the others. Temporal stability of the large-scale circulation subjects allows us to show dynamic evolution, and to take it into account when developing a scheme of middle-range forecast methods (3-10 days in advance).